Machinery of wooden housing industry in the Brazilian State of São Paulo - De Araujo, Victor [UNESP]; Gava, Maristela [UNESP]; Vasconcelos, Juliano [UNESP]; Morales, Elen [UNESP]; Alves, Paulo [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Gonçalves, Marcos Tadeu [UNESP]; Garcia, José [UNESP] (My University, 2016)
Despite the promising future to industry in Brazil, most production sectors still suffer with the access to newer industrial technologies. Some very specific and limited incentives have been offered by the local Government to stimulate these companies. However, the forestry-timber sector hardly has access them, due to the several barriers and bureaucracies. Together with other factors, it is a visible reason to the lack of the renovation of their production lines, as well as the improvement of their industrial technologies. Industrial parks with modern technology contribute directly to products which better quality, and it could be a favourable way to the Brazilian development in industrial aspect. For that reason, it is important to perform studies to stimulate this sector. This study aims to verify the situation of the timber machinery of the wooden housing manufacturers in the Brazilian State of São Paulo. It was realized through a survey applied directly to the companies' owners. This work revealed that the largest share of these companies of São Paulo State presented update equipment to produce wooden houses. Nevertheless, these companies still could improve the technology of their manufactures with robotic and automated machinery, looking for a better productivity.
Keywords: Industrial equipment; São Paulo State; Timber industry; Wooden houses